Multidimensional vocal assessment after laser treatment for recurrent respiratory papillomatosis. (12th August 2016) - Kono, Takeyuki; Yabe, Haruna; Uno, Kosuke; Saito, Koichiro; Ogawa, Kaoru
Abstract : Objectives/Hypothesis: Recurrent respiratory papillomatosis (RRP) is a benign epithelial tumor that exhibits a high frequency of recurrence. This study assesses the vocal function after laser treatment for RRP, particularly in relation to the frequency of surgery. Study Design: Retrospective study. Methods: Thirty RRP patients who underwent laser surgery that controlled the tumor were included. Preoperative and postoperative Grade, Roughness, Breathiness, Asthenia, and Strain Scale, videostroboscopic findings, aerodynamic and acoustic parameters, and self‐assessment questionnaires were measured and compared with an age‐ and sex‐matched control group. Subsequently, to evaluate the association between postoperative voice quality and the number of surgeries, the patients were divided into three groups (group 1: single surgery, group 2: 2–5 surgeries, group3: >6 surgeries), and comparative multidimensional vocal assessments were performed. Results: The mean number of surgeries was 3.4 (range, 1–8). Although all patients exhibited poorer vocal function than the control group preoperatively, they showed improvement in postoperative subjective and objective parameters. However, four patients who underwent one surgery with relatively aggressive ablation exhibited vocal cord scarring and deteriorated objective parameters. All remaining patients showed voice quality that was on par with the control group. Subgroup analysis proved no association between post‐therapeutic voice quality and the patient characteristics, including preoperative staging and the number of surgical treatments performed. Conclusions: RRP patients can achieve a close to normal voice with high satisfaction even after recurrent surgical treatment when ablation of a subepithelial lesion using sufficient laser energy is adequate. Level of Evidence: 3b Laryngoscope, 127:679–684, 2017